摆动齿轮箱自动压紧摩擦驱动旋转舞台 - 陈德生; 潘浓芬 (Jixie chuandong)
This paper introduces the working principle and characteristics of the rotary stage driven by friction force and the pressure for friction force provided by the swinging gear box automatically in detail. And it also presents the methods of main parameters selection and calculation.